2001
DOI: 10.1002/1097-4636(20010605)55:3<387::aid-jbm1027>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on bioactive glass microstructure, corrosion behavior, ? potential, and protein adsorption

Abstract: Bioactive glass ceramic is characterized by high mechanical strength and a slow rate of bone bonding. To understand the factors contributing to a decrease in the rate of bone bonding to bioactive glass ceramic, we evaluated the effect of different percentages of bioactive glass crystallization on corrosion behavior, zeta potential, and serum protein adsorption. X-ray diffraction analysis showed that heat treatment of bioactive glass in the temperature range 550 degrees -700 degrees C resulted in the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 28 publications
7
46
1
Order By: Relevance
“…An earlier study indicated that the apatite-forming ability of glasses is higher than glass-ceramics with the same chemical composition, due to lower solubility of crystalline phase. This could be attributed to the strong bond between atoms in the crystal lattice [2,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study indicated that the apatite-forming ability of glasses is higher than glass-ceramics with the same chemical composition, due to lower solubility of crystalline phase. This could be attributed to the strong bond between atoms in the crystal lattice [2,70].…”
Section: Discussionmentioning
confidence: 99%
“…dissolution of silica phase and phosphate phase, affecting the glass bioactivity. It was shown that phase separation reduced the solubility of Si and Ca ions from the bioactive glass, which can be attributed to the increase in viscosity of the phase-separated glass compared to the homogeneous one [70].…”
Section: Discussionmentioning
confidence: 99%
“…1 The first bioactive glasses made of sodium oxide, calcium oxide, phosphorous pentoxide and silicon dioxide were found to phase separate and crystallize easily during working processes in the temperature range between glass transformation and liquidus. 2 The energy provided from heating during working processes assists in breaking bondings in the glass network structure and thus facilitates arranging the melt into crystal structures in this instable region. Compared to traditional glasses bioactive glasses have a high amount of network modifiers and a low amount of silica network formers, thus giving smaller structural units.…”
Section: Introductionmentioning
confidence: 99%
“…They are excellent biomaterials because they are nontoxic, they match the composition of natural bone, and show excellent integration with bone in the framework of in vitro and in vivo studies.1 Unfortunately, the low toughness of bioactive glass has limited its use to non-load-bearing applications [8,9]. Crystallization of bioactive glasses may be the best way to improve their mechanical properties [8,10,11]. It has been reported [12] that some glass-ceramics in the CaO-SiO 2 -P 2 O 5 -Na 2 O system, containing apatite and wollastonite phases, with good mechanical properties and the ability of forming tight chemical bonds with living bone can be produced through sintering and subsequent crystallization of glass powders.…”
Section: Introductionmentioning
confidence: 99%